2019
DOI: 10.1016/j.jad.2018.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Suicide deaths by gas inhalation in Toronto: An observational study of emerging methods of suicide

Abstract: Suicide by inhalational asphyxia, particularly by compressed gases, has increased substantially over time in Toronto consistent with observations in other countries. Increased surveillance of these deaths, efforts to restrict access to these methods, and timely interventions including minimizing media reporting are all warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 45 publications
1
13
0
2
Order By: Relevance
“…In the United States, charcoal burning suicide has rarely been reported (Azrael et al, 2016); however, a study exploring trends in carbon monoxide inhalation in King county, Washington, found that the proportion of charcoal burning suicides increased from less than 15% in 1996–1998 to as high as 40% in 2005–2009 (Schmitt et al, 2011). In Toronto, Canada, charcoal burning suicide cases increased by 533% from 3 cases in 1998–2003 to 16 cases in 2010–2015 (Sinyor et al, 2019). Meanwhile, charcoal burning suicide cases were mainly Asian ethnically in Toronto (Sinyor et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, charcoal burning suicide has rarely been reported (Azrael et al, 2016); however, a study exploring trends in carbon monoxide inhalation in King county, Washington, found that the proportion of charcoal burning suicides increased from less than 15% in 1996–1998 to as high as 40% in 2005–2009 (Schmitt et al, 2011). In Toronto, Canada, charcoal burning suicide cases increased by 533% from 3 cases in 1998–2003 to 16 cases in 2010–2015 (Sinyor et al, 2019). Meanwhile, charcoal burning suicide cases were mainly Asian ethnically in Toronto (Sinyor et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In Toronto, Canada, charcoal burning suicide cases increased by 533% from 3 cases in 1998–2003 to 16 cases in 2010–2015 (Sinyor et al, 2019). Meanwhile, charcoal burning suicide cases were mainly Asian ethnically in Toronto (Sinyor et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…These findings that the former have decreased and the latter increased over time are encouraging. The previous study also found that articles about asphyxia other than by motor vehicle exhaust were associated with a subsequent increase in suicides in Toronto (Sinyor et al, 2018a), which is a concern given that reporting on this method has increased over time as have deaths by this method (Sinyor et al, 2019). This finding reinforces the need for the recommendation that journalists avoid disseminating novel or unusual suicide methods put forward in the updated iteration of the CPA guidelines (Sinyor et al, 2018b) as well as other international guidelines (Samaritans, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Entre 1998 y 2015 hubo 4 062 muertes por suicidio en Toronto -Canadá, de las cuales 4.7% fueron por asfixia por inhalación de gases; estas muertes incluyeron gas comprimido, gases por escape de vehículos motorizados y gases por quema de carbón. Actualmente las muertes por quema de helio y carbón todavía representan el 4.2% del total de suicidios entre el 2010-2015 [35].…”
Section: Américaunclassified
“…1°, 2°, 3°: orden de frecuencia del método preferido en cada país Fuente: Artículos revisados[3,7,15,20,28,[30][31][32][33][34][35]38].Elaboración: Los autores.Tabla 2.…”
unclassified